2019
DOI: 10.3390/biom9100577
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Toxicology Approach to Screen the Hepatotoxic Ingredients in Traditional Chinese Medicines: Polygonum multiflorum Thunb as a Case Study

Abstract: In recent years, liver injury induced by Traditional Chinese Medicines (TCMs) has gained increasing attention worldwide. Assessing the hepatotoxicity of compounds in TCMs is essential and inevitable for both doctors and regulatory agencies. However, there has been no effective method to screen the hepatotoxic ingredients in TCMs available until now. In the present study, we initially built a large scale dataset of drug-induced liver injuries (DILIs). Then, 13 types of molecular fingerprints/descriptors and eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Small molecules were predicted against rheumatoid arthritis using an integrated approach of ML and DL [ 147 ]. Another study performed using an AI-based method identified the hepatotoxic ingredient from Chinese traditional medicine [ 148 ]. Predictive models have been developed for screening liver toxicity induced due to drugs using ML algorithms [ 110 ].…”
Section: Artificial Intelligence Methods and Their Role In Drug Discoverymentioning
confidence: 99%
“…Small molecules were predicted against rheumatoid arthritis using an integrated approach of ML and DL [ 147 ]. Another study performed using an AI-based method identified the hepatotoxic ingredient from Chinese traditional medicine [ 148 ]. Predictive models have been developed for screening liver toxicity induced due to drugs using ML algorithms [ 110 ].…”
Section: Artificial Intelligence Methods and Their Role In Drug Discoverymentioning
confidence: 99%
“…MACCS (Molecular ACCess System) Keys are another of the most used structural keys [36] , [37] , [39] , [38] . Sometimes they are known as MDL keys, which bear the name of the company that developed them.…”
Section: The Importance Of Input Data In Machine Learning Predictionsmentioning
confidence: 99%
“…They are fingerprints based on topological routes, which represent all possible connectivity routes defined by a specific fingerprint through an input compound [36] , [39] , [37] , [41] . They mainly focus on chemical connectivity information of synthetic compounds.…”
Section: The Importance Of Input Data In Machine Learning Predictionsmentioning
confidence: 99%
“…Hopkins proposed the concept of “network pharmacology” and it’s becoming increasingly popular among researchers in recent years ( Tang et al, 2020 ; Xu J. et al, 2019b ). The characteristic of network pharmacology is following the holistic theory of TCM(S. He et al, 2019b ). The basic opinion of network pharmacology is well suited for exploring the mechanisms of multi-components and multi-targets drugs, so it is an ideal approach in investigating and identifying the mechanism of the TCM formula ( Guo et al, 2019 ; Huang et al, 2020 ; Liu et al, 2020 ; Zhang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%